Fundamentals of Curvilinear Ferromagnetism: Statics and Dynamics of Geometrically Curved Wires and Narrow Ribbons. Issue 12 (19th January 2022) - Sheka, Denis D.; Pylypovskyi, Oleksandr V.; Volkov, Oleksii M.; Yershov, Kostiantyn V.; Kravchuk, Volodymyr P.; Makarov, Denys
Abstract: Low‐dimensional magnetic architectures including wires and thin films are key enablers of prospective ultrafast and energy efficient memory, logic, and sensor devices relying on spin‐orbitronic and magnonic concepts. Curvilinear magnetism emerged as a novel approach in material science, which allows tailoring of the fundamental anisotropic and chiral responses relying on the geometrical curvature of magnetic architectures. Much attention is dedicated to magnetic wires of Möbius, helical, or DNA‐like double helical shapes, which act as prototypical objects for the exploration of the fundamentals of curvilinear magnetism. Although there is a bulk number of original publications covering fabrication, characterization, and theory of magnetic wires, there is no comprehensive review of the theoretical framework of how to describe these architectures. Here, theoretical activities on the topic of curvilinear magnetic wires and narrow nanoribbons are summarized, providing a systematic review of the emergent interactions and novel physical effects caused by the curvature. Prospective research directions of curvilinear spintronics and spin‐orbitronics are discussed, the fundamental framework for curvilinear magnonics are outlined, and mechanically flexible curvilinear architectures for soft robotics are introduced. Abstract : A critical review of the theoretical understanding of the curvilinear magnetism of rigid and mechanically flexible (helimagnetic) nanowires and nanoribbons is provided. The review summarizes in an accessible manner the complex theoretical ideas on the emergent interactions, outlines novel physical effects and addresses relevance of these low‐dimensional architectures for curvilinear spintronics, curvilinear spin‐orbirtonics, and curvilinear magnonics.